A Case Report on Friedreich’s Ataxia - G. Ragesh (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Friedreich’s ataxia is a genetic disorder that causes certain nerve cells to weaken over time. Gene mutation at 9q13 and 9p23-p11. GAA trinucleotide repeats expansion of intron 1 from 70 to more than 1000 GAA triplets, and uncontrollable decreased vitamin E levels. Friedreich’s ataxia also affects the heart, bones and pancreas cells that produce insulin. Loss of coordination, fatigue, vision impairment, aggressive scoliosis, DM and serious heart condition (cardiomyopathy) are the major signs and symptoms. This is a case review presenting: A 25-year-old male patient admitted in a general medicine with the chief complaints of breathlessness and pedal edema since 10 days and he was previously treated for upper respiratory tract infection. The patient was swaying to the right associated with curvature of the spine. These symptoms progressed slowly and then noticed to have difficulty in lifting both upper and lower limbs simultaneously in both proximal and distal regions. Difficulty in turning in bed, deterioration of vision since last three years, presently only able to appreciate light. He was found to have high sugar level since last year. Past medical history reveals that known case of DM and dilated cardiomyopathy since one year. Based on the patient medical history, physical examination, neurologic examination, neuroimaging, three-generation family history, and molecular genetic testing the patient complaints were diagnosed as friedreich’s ataxia. Patient initially managed with symptomatically followed by physical therapy. Antioxidant such as vitamin E, coenzyme q10 and idebenone were given to delay the disease progression. Medications to lower the blood sugar, heart disease (ACE inhibitor) prescribed to reduce the co-morbidities with Friedrich’s ataxia. Surgery is preferred to correct bony deformities. The patient improved after 17 days of therapy. Patient discharged on request and advised to go for eye check-up. Regular physiotherapy and speech therapy recommended improving their cognitive functions.